2011
DOI: 10.1007/s12602-011-9066-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum 299v Prevents Caspase-Dependent Apoptosis In Vitro

Abstract: Selective microbes used as probiotics can enhance epithelial cell protection. We have previously shown that a Lactobacillus plantarum strain 299v (Lp299v) has the ability to induce mucin genes. In the current study, we utilized a cytokine model of inflammation in cell culture to study the modulation of apoptosis by this probiotic. HT-29 cells were pre-incubated with the Lp299v or L. plantarum strain adh- (Lpadh-), a non-adherent derivative of Lp299v. Cells were challenged with a mixture of cytokines (TNF-α, IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Also, effect of probiotic Lb . plantarum 299v on cytokine-induced apoptosis was evaluated [42]. The authors demonstrated that cell pre-incubation with Lb .…”
Section: Discussionmentioning
confidence: 99%
“…Also, effect of probiotic Lb . plantarum 299v on cytokine-induced apoptosis was evaluated [42]. The authors demonstrated that cell pre-incubation with Lb .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dykstra and collaborators showed that the interaction of this probiotic strain with the cells was responsible to enhance the cellular-driven protection via reduction of the caspase pathway activation [ 23 ]. The importance of mucins was also highlighted by other observations demonstrating a reduced number of Goblet cells in inflammatory lesions of the GIT as well as a decreased functional capacity of the mucins to bind pro-inflammatory molecules and to inhibit bacterial binding in the inflamed colon [ 30 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…64 L. plantarum (strain 299v) has the capacity to enhance the production and secretion of mucins (MUC2 and MUC3) from human intestinal (HT-29) epithelial cells. 65 Probiotic mixtures also increase MUC2 gene expression and mucin protein secretion in rat colon. 66 L. rhamnosus GG-derived soluble proteins (p40 and p70) ameliorate intestinal injury and inflammation by inhibiting epithelial cell apoptosis 67 and increasing mucin production through transactivation of the epidermal growth factor receptor.…”
Section: Probiotics Enhance Intestinal Barrier Functionmentioning
confidence: 97%
“…L. plantarum (strain 299v) has the capacity to enhance the production and secretion of mucins (MUC2 and MUC3) from human intestinal (HT‐29) epithelial cells . Probiotic mixtures also increase MUC2 gene expression and mucin protein secretion in rat colon .…”
Section: Preclinical Trials and Mechanism Of Action In Inflammatory Dmentioning
confidence: 99%